Flexing dalam Pandangan Islamic Behavioral Finance - Wida Utami; Agung Abdullah (Jurnal Ilmiah Ekonomi Islam, 2023)
Flexing or a narcissistic behavior by showing off the wealth its really happened a lot lately on social media. Flexing is an interesting topic of conversation among the public. Sometimes flexing is the behavior to made a perspectives done by fake rich people. This study is aims to determine the flexing behavioral on Islamic economics perspective. The method in this study is qualitative, with the analysis on a phenomenological approach. In this study it was found that flexing is prohibited in Islam Economic perspective. Flexing is done by fake rich people to show their existence or to gain recognition from others. People who are truly wealthy tend to exhibit good financial behavior and are able to live simply without spending too much money. In Islam, it is recommended to live a simple and balanced life and not to waste wealth in order to fulfill desires. Islam also encourages its people to prioritize saving rather than using their finances to fulfill desires rather than needs, such as being more concerned with saving, investing, or helping people who are experiencing difficulties by zakah, infaq and sedekah. Therefore, financial intelligence is very important for every individual in order to avoid the behavior of showing off wealth. Financial intelligence is related to knowledge, behavior in managing, using assets so that they become more blessed and do not violate sharia provisions.